A study on the improvement of sanitation in the U.P cooperative canteen - Burlat, Jorge C.; Cruz, Agerico V. (1992.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Food service -- Sanitation -- Philippines